2010
DOI: 10.1080/09540120903499196
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and sustainability of care facilitators engaged in a community home-based HIV/AIDS program in Masvingo Province, Zimbabwe

Abstract: Community home-based HIV/AIDS programs with care facilitators (CFs) are key interventions for dealing with both the shortage of health professionals (e.g., physicians, nurses, midwives, etc.) and the current HIV/AIDS epidemic in many parts of Africa. Zimbabwe, one of the sub-Saharan countries is not an exception. The Zimbabwe Red Cross Society started a community home-based HIV/AIDS program with CFs in 1992. This paper describes the results of a cross-sectional study conducted to examine the factors influencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…In some cases, lack of supplies resulted in not being able to conduct the job ( Furth and Crigler 2012 ; Kalyango et al 2012 ). However, Osawa et al (2010) found no correlation between supplies and motivational outcome of CFs in Zimbabwe and in Kenya, no correlation was found between adequacy of medicine supplies in the village and guideline adherence of CHWs ( Rowe et al 2007a ).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In some cases, lack of supplies resulted in not being able to conduct the job ( Furth and Crigler 2012 ; Kalyango et al 2012 ). However, Osawa et al (2010) found no correlation between supplies and motivational outcome of CFs in Zimbabwe and in Kenya, no correlation was found between adequacy of medicine supplies in the village and guideline adherence of CHWs ( Rowe et al 2007a ).…”
Section: Resultsmentioning
confidence: 92%
“…CHWs who reported to enjoy more social prestige were more than three times as likely to remain. A cross-sectional study on Care Facilitators (CFs) working in HIV home-based care in Zimbabwe found that the more the communities accepted, appreciated and supported the CFs in their activities, the more CFs were motivated to perform ( Osawa et al 2010 ). Rowe et al (2007) found that CHWs working in child health in Kenya showed better guideline adherence when they reported to receive respect from the community.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of financial or material compensation for services rendered could lead to an inability of CHWs to provide for their family and is particularly exacerbated in areas of pervasive poverty [ 62 ]. The willingness to become a CHW could be influenced by the wish to earn an income or the hope of being compensated eventually, especially in situations where there is high unemployment or fewer opportunities [ 64 , 76 - 78 ]. For example, a study on CBDs in Uganda reported that, due to high levels of unemployment, people volunteered hoping that they would be remunerated eventually [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…CHWs have been assigned diverse roles and activities throughout their history, both within and across countries, targeting a wide range of preventive, curative and/or developmental interventions (Gilmore & McAuliffe, 2013). CHWs are seen as pivotal in increasing accessibility to Primary Healthcare (PHC) services (Osawa, Kodama, & Kundishora, 2010).…”
mentioning
confidence: 99%